Data Resource Profile: Pathways to Health and Social Equity for Children (PATHS Equity for Children). (11th September 2014) - Nickel, Nathan C; Chateau, Dan G; Martens, Patricia J; Brownell, Marni D; Katz, Alan; Burland, Elaine MJ; Walld, Randy; Hu, Mingming; Taylor, Carole R; Sarkar, Joykrishna; Goh, Chun Yan; ,
Abstract : The PATHS Data Resource is a unique database comprising data that follow individuals from the prenatal period to adulthood. The PATHS Resource was developed for conducting longitudinal epidemiological research into child health and health equity. It contains individual-level data on health, socioeconomic status, social services and education. Individuals' data are linkable across these domains, allowing researchers to follow children through childhood and across a variety of sectors. PATHS includes nearly all individuals that were born between 1984 and 2012 and registered with Manitoba's universal health insurance programme at some point during childhood. All PATHS data are anonymized. Key concepts, definitions and algorithms necessary to work with the PATHS Resource are freely accessible online and an interactive forum is available to new researchers working with these data. The PATHS Resource is one of the richest and most complete databases assembled for conducting longitudinal epidemiological research, incorporating many variables that address the social determinants of health and health equity. Interested researchers are encouraged to contact [mchp_access@cpe.umanitoba.ca ] to obtain access to PATHS to use in their own programmes of research.